Electrochemical Performance Enhancement of 3D Printed Electrodes Tailored for Enhanced Gas Evacuation during Alkaline Water Electrolysis. Issue 1 (7th November 2022) - Rocha, Fernando; Delmelle, Renaud; Georgiadis, Christos; Proost, Joris
Abstract: A zero‐gap cell with porous electrodes is a promising configuration for alkaline water electrolysis. However, gas evacuation becomes a challenge in that case, as bubbles can get trapped within the electrode's 3D structure. This work considers a number of 3D printed electrode geometries with so‐called triply periodic minimal surfaces (TPMS). The latter is a mathematically defined structure that repeats itself in three dimensions with zero mean curvature, and can therefore be expected to be particularly well‐suited to enhance gas evacuation. Another advantage as compared to other state‐of‐the‐art 3D electrodes like foams or felts lies in the fact that their porosity, which determines the available surface area, and their pore size or flow channel dimensions, which determines the degree of bubble entrapment, can be varied independently. By a combined experimental and modeling approach, this work then identifies the structural parameters that direct the performance of such 3D printed TPMS geometries toward enhanced gas evacuation. It is demonstrated that an optimal combination of these parameters allows, under a forced electrolyte flow, for a reduction in cell overpotential of more than 20%. This indicates that efforts in optimizing the electrode's geometry can give a similar electrochemical performance enhancement as optimizing its electro‐catalytic composition. Abstract : During water electrolysis on 3D electrodes, gas bubbles can get trapped; this work evaluates 3D printed electrode geometries with triply periodic minimal surfaces (TPMS); a combined experimental and modeling approach identifies the TPMS structural parameters that minimize bubble entrapment; under forced electrolyte flow, the cell overpotential can be reduced by more than 20%.